Data Reading Based on the IIO Subsystem Framework - Pang, Wei (International Journal of Computer Science and Information Technology, 2024)
This document outlines how to read data from the ICM-20608 sensor using the i.MX 6ULL application processor within the IIO framework on a Linux system. The i.MX 6ULL is an application processor from NXP Semiconductors based on the ARM Cortex-A7 architecture, designed specifically for low-power and high-performance embedded applications. The ICM-20608 is a high-performance six-axis sensor that integrates a three-axis gyroscope and a three-axis accelerometer, widely used in motion detection and attitude estimation.